2022
DOI: 10.1097/mot.0000000000000972
|View full text |Cite
|
Sign up to set email alerts
|

Potential options to expand the intestinal donor pool: a comprehensive review

Abstract: Purpose of reviewIntestinal donation is currently restricted to ‘perfect’ donors, as the intestine is extremely vulnerable to ischemia. With generally deteriorating donor quality and increasing indications for intestinal transplantation (ITx), the potential to safely increase the donor pool should be evaluated.Recent findingsIncreasing awareness on intestinal donation (often forgotten) and cautiously broadening the strict donor criteria (increasing age, resuscitation time and ICU stay) could expand the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 55 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…41,42 There have been no reported deaths or major complications. [43][44][45][46][47][48] Wu et al reported in 40 donors 1 intraoperative bleeding, 1 small bowel obstruction (conservatively treated), and 1 incisional hernia. 48 Donor´s weight decreased during the first months postoperatively, but was restored at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 There have been no reported deaths or major complications. [43][44][45][46][47][48] Wu et al reported in 40 donors 1 intraoperative bleeding, 1 small bowel obstruction (conservatively treated), and 1 incisional hernia. 48 Donor´s weight decreased during the first months postoperatively, but was restored at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent data from the International Intestinal Transplant Registry (ITR), only 78 (1.9%) out of 4156 patients transplanted up to September 2019 worldwide have been reported as living donors. 6 Despite potential risks to the donor, living-organ donation can offer substantial advantages over the deceased donation, particularly in terms of the elective nature of the procedure, better HLA matching, shorter cold ischemia times, and reduced waiting times. Moreover, the use of living donors can provide greater opportunity to implement desensitization protocols in the setting of highly sensitized ITx candidates.…”
mentioning
confidence: 99%
“…The published results of retrospective case reports and case series are limited by the small numbers of patients, study methods, and a lack of donor and recipient long-term outcomes. 6 , 10 Although preliminary outcomes appear encouraging, the role of LDITx has not yet been established. From 1999 to 2021, our team has performed 40 LDITx procedures and hereby we report our short-term and intermediate-term clinical outcomes of recipients after this procedure.…”
mentioning
confidence: 99%
See 2 more Smart Citations